2019
DOI: 10.1002/etc.4359
|View full text |Cite
|
Sign up to set email alerts
|

Higher silver bioavailability after nanoparticle dietary exposure in marine amphipods

Abstract: On release into surface waters, engineered silver nanoparticles (AgNPs) tend to settle to sediments and, consequently, epibenthic fauna will be exposed to them through diet. We established Ag uptake and accumulation profiles over time in the hemolymph of a marine amphipod fed with a formulated feed containing AgNPs or AgCl. Silver bioavailability was higher in organisms exposed to AgNPs, indicating that the nanoparticles pose a higher risk of toxicity compared to similar concentrations of AgCl. Environ Toxicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Ag uptake rates and concentration in the haemolymph of the marine amphipod Parhyale hawaiensis were described by Vannuci-Silva et al (2018;2019). Authors indicated that animals exposed via food containing AgCl would require more than 100 days to uptake similar amounts of silver absorbed by organisms exposed via water for only 96 hours (Vannuci-Silva et al, 2019). For food containing AgNP, a 30 to 40 days period would be necessary to reach the same silver internal concentration than a 96-hour exposure via water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ag uptake rates and concentration in the haemolymph of the marine amphipod Parhyale hawaiensis were described by Vannuci-Silva et al (2018;2019). Authors indicated that animals exposed via food containing AgCl would require more than 100 days to uptake similar amounts of silver absorbed by organisms exposed via water for only 96 hours (Vannuci-Silva et al, 2019). For food containing AgNP, a 30 to 40 days period would be necessary to reach the same silver internal concentration than a 96-hour exposure via water.…”
Section: Discussionmentioning
confidence: 99%
“…Free silver ion (Ag + ) is the main species responsible for Ag toxicity in the aqueous phase, belonging to the 4 highest toxicity class together with Cd, Cr(VI) and Hg (Ratte, 1999 and references therein). However, for AgNP, it is still unclear if toxicity is due only to the dissolution of Ag + or whether the nanoparticles size, shape and defects in surface crystals contribute to their high toxicity (George et al, 2012;Vannuci-Silva et al, 2019). Once in the marine ecosystem, silver and its nanoparticles tend to agglomerate and precipitate to the sediment bottom (Forstner, 1983), leading to elevated exposure of benthic organisms such as amphipods.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increasing interest in the use of the marine amphipod Parhyale hawaiensis in ecotoxicology (Artal et al, 2018, 2019; Botelho et al, 2022; dos Santos, Botelho, et al, 2022; Dos Santos, Vannuci‐Silva, et al, 2022; Vacchi et al, 2019; Vannuci‐Silva et al, 2018, 2019) and in other sciences (Paris et al, 2022; Rehm et al, 2009), we here describe their hemocyte characteristics and identify the various cell types and their proportions, as well as their ability to phagocytize bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…9 Meanwhile, AgNP waste is inevitably generated in the process from production to disposal and accumulated in the environment, increasing the organism exposure risk. [9][10][11][12][13] AgNPs can penetrate the skin through wound dressing and textile products 14 and be inhaled into the body by spraying. 15 It has been reported that AgNPs can cause DNA damage in human cells.…”
Section: Introductionmentioning
confidence: 99%